Search engine failure : finding problems in relevant results. - Lim, Daniel Boon Chye. (2008)
This dissertation provided an appreciation of whether Internet search engines appropriately provided an adequate number of relevant search engine results to its Internet users which were also free from any untoward legality. An empirical study was conducted to address the following research questions: (1) whether Internet search engines have failed to adequately retrieve and rank content-relevant search results despite their claim; (2) whether these search results were free from the effects of search engine spam and other means of tweaking web pages to raise their rankings in the search results; and (3) whether search engines retrieved search results that conveniently pointed users to sources of illegal copies of multimedia content.